Managing Water Infrastructures in the Berlin-Brandenburg Region between Climate Change, Economic Restructuring and Commercialisation - Hüesker, Frank; Moss, Timothy; Naumann, Matthias (DIE ERDE – Journal of the Geographical Society of Berlin, 2011)
Global change is posing a major challenge to existing forms of natural resource use, socio-economic development and institutional regulation. Although trends such as climate change, socio-economic transformation and institutional change are global in their scope, they have very specific regional outcomes. Regionally distinct coping strategies are required which take into account both the diversity of regional impacts of global change and the local contexts of appropriate responses. This paper explores the impacts of global change on the management of water infrastructure systems in the Berlin-Brandenburg region in terms of three concurrent and overlapping challenges: climate change, socio-economic change and institutional change. It subsequently examines how regional actors in the water sector are addressing these three dimensions of global change.